Strategi Guru PAI Dalam Meningkatkan Minat Belajar Dan Praktik Keagamaan Siswa - Yanti; Adila Adha; Fitra Anisa (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
Islamic Religious Education has an important role in increasing learning interest and shaping students’ religious practices, however in reality there is still a low level of learning interest and religious practices of students in elementary schools that are not yet optimal. Therefore, appropriate strategies from Islamic Religious Education teachers are needed to overcome these problems. This study aims to analyze the strategies of Islamic Religious Education teachers in increasing learning interest and religious practices of students at SDN 003 Tebing. This study uses a descriptive qualitative approach with Islamic Religious Education teachers as the main informants. Data collection techniques were carried out through observation, interviews, and documentation, while data analysis used an interactive model which includes data reduction, data presentation, and conclusion drawing with validity testing through source and method triangulation. The results of the study show that the teacher's strategies in increasing students’ learning interest are carried out through the use of varied teaching methods, providing motivation, and relating material to daily life, while strategies in increasing religious practices are carried out through habituation of religious activities and teacher exemplification. There are supporting factors in the form of school support and a conducive learning environment as well as inhibiting factors in the form of limited time, facilities and infrastructure, and differences in student motivation. Overall, the strategies of Islamic Religious Education teachers implemented are quite effective in increasing students’ learning interest and religious practices, though further development and optimization efforts are still needed so that the results achieved are more maximal.